A Novel Route for Development of Bulk Al/SiC Metal Matrix Nanocomposites - Payodhar Padhi; Sachikanta Kar (Journal of Nanotechnology)
Addition of nano particles, even in quantities as small as 2 weight percent can enhance the hardness or yield strength by a factor as high as 2. There are several methods for the production of metal matrix nanocomposites including mechanical alloying, vertex process, and spray deposition and so forth. However, the above processes are expensive. Solidification processing is a relatively cheaper route. During solidification processing, nano particulates tend to agglomerate as a result of van der Waals forces and thus proper dispersion of the nano particulate in metal matrix is a challenge. In the present study a noncontact method, where the ultrasonic probe is not in direct contact with the liquid metal, was attempted to disperse nanosized SiC particulates in aluminum matrix. In this method, the mold was subjected to ultrasonic vibration. Hardness measurements and microstructural studies using HRTEM were carried out on samples taken from different locations of the nanocomposite ingot cast by this method.